Integrating Immunologic Signaling Networks: The JAK/STAT Pathway in Colitis and Colitis-Associated Cancer - Zundler, Sebastian; Neurath, Markus (Vaccines, 2016)
Cytokines are believed to be crucial mediators of chronic intestinal inflammation in inflammatory bowel diseases (IBD) such as Crohn's disease (CD) and ulcerative colitis (UC). Many of these cytokines trigger cellular effects and functions through signaling via janus kinase (JAK) and signal transducer and activator of transcription (STAT) molecules. In this way, JAK/STAT signaling controls important events like cell differentiation, secretion of cytokines or proliferation and apoptosis in IBD in both adaptive and innate immune cells. Moreover, JAK/STAT signaling, especially via the IL-6/STAT3 axis, is believed to be involved in the transition of inflammatory lesions to tumors leading to colitis-associated cancer (CAC). In this review, we will introduce the main cellular players and cytokines that contribute to pathogenesis of IBD by JAK/STAT signaling, and will highlight the integrative function that JAK/STATs exert in this context as well as their divergent role in different cells and processes. Moreover, we will explain current concepts of the implication of JAK/STAT signaling in CAC and finally discuss present and future therapies for IBD that interfere with JAK/STAT signaling.
EVALuna2:2080